Crops on the edge: Mechanisms and strategies for yield stability in challenging climates - Sheershika; Prasanna, G; Gopal, Narkhede; Shourabh, Joshi; Pusarla, Susmitha; Rama, Devi B; Aman, Tutlani; Vivek, Kumar Pathak; Tajamul, Aziz Alaie; Vishal, Kumar Gupta; Subhashree, Das (Plant Science Today, 2026)
Climate change has emerged as a major constraint to global crop productivity by intensifying abiotic and biotic stresses such as drought, heat, flooding, nutrient limitations and pest disease pressures, thereby threatening yield stability across agro-ecosystems. The primary objective of this review is to critically synthesise contemporary genetic, genomic, physiological, biotechnological and agronomic strategies that enhance crop yield stability under challenging climatic conditions. The review systematically integrates evidence from recent advances in molecular breeding, marker-assisted and genomic selection (GS), genome editing technologies (particularly CRISPR/Cas systems) and functional genomics with plant physiological mechanisms including root system architecture, water-use efficiency (WUE), osmoprotectant accumulation and stress-adaptive morphological traits. Key findings indicate that yield stability is best achieved through multi-trait and multi-scale approaches that combine stress-tolerant genetics with optimised resource-use efficiency, resilient seed systems and climate-smart agronomic practices. The synthesis further highlights the role of pest and disease resistance, nutrient-use efficiency and flood-tolerance mechanisms as integral components of resilient cropping systems rather than isolated traits. In conclusion, the review demonstrates that integrated, systems-based strategies are essential for sustaining crop productivity under climate variability. Future perspectives emphasise the convergence of artificial intelligence-assisted breeding, microbiome engineering, speed breeding and supportive policy frameworks to accelerate the deployment of climate-resilient cultivars and ensure long-term food security in an era of increasing climatic uncertainty.